Implementation of Modern Monetary Theory Through Printing Money as an Economic Stimulus Solution Islamic Perspective - Nurfaedah, Nurfaedah; Mustikasari, Molly; Abdullah, Muhammad Bin (Universitas Islam Negeri Raden Intan Lampung, 2022)
The current Covid-19 pandemic has caused the global economy to stagnate. A significant decline in the rate of economic growth was experienced by almost every country, including Indonesia. Printing money is one solution, but an in-depth study needs to be done considering that there are differences in success when implemented, one of which is in European countries, Indonesia and Zimbabwe. For this reason, the purpose of this paper is to conduct an in-depth study of the correct understanding, mechanism, and application of printing money that can stimulate economic growth from an Islamic perspective. This research approach uses literature study, in collecting data by understanding and studying theories from various literature related to this research. The results of the study indicate that- to solve the problem of the economic crisis, can be overcome by using a printing money policy. This policy has been successfully implemented in developed countries such as America, China, and several European countries so that they can get out of the crisis. The reason for its success is by taking into account the following points: first, the understanding of the modern MMT theory and the traditional MMT theory that both theories agree on the MMT derivative product namely printing money, only that modern MMT accompanies the project-based policy. Second, using the right mechanism where money is used according to its function in the Islamic perspective as a medium of exchange and standard prices where the application of printing money is project-based and is not used to cover consumptive government spending so that the amount of money in circulation depends on the number of goods and services. In production, this condition does not cause inflation. Third, the implementation of printing money is channeled to productive government needs. Automatically the circulation of money in circulation according to the number of goods and services produced.